The Role of Islamic Religious Education in Shaping the Character of Students’ at SMAS NWDI Korleko - Sahwan; Rizal, Syamsul (Jurnal Penelitian Tarbawi: Pendidikan Islam dan Isu-Isu Sosial, 2026)
Islamic Religious Education plays a crucial role in shaping the Islamic character of students at SMAS NWDI Korleko. Through well-planned instruction, teachers not only deliver knowledge but also guide and instill Islamic values so that students are able to understand, internalize, and practice these teachings in their daily lives. This study employs a qualitative approach using a case study design, with data collected through interviews, observations, and document analysis. Islamic Religious Education is expected to contribute significantly to the formation of a morally responsible society with strong Islamic character. Therefore, it serves as a long-term investment in producing individuals who are not only intellectually capable but also possess noble character in accordance with Islamic values. Keywords: islamic religious education, islamic character